RIA Technologies - Web-Based Business Applications Development - Bryndza, Joanna (Advanced Information Technologies for Management – AITM 2009, 2009)
The author describes RIA technologies: Flash and Silverlight. These technologies are used in business Internet applications. Modem trends of developing information systems are based on SaaS model (Software-as-a-Service). Growing popularity of Internet applications causes that RIA technologies will be more important in the future.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 85, s. 20-27